Setting savings free: Proposals for the taxation of savings and profits - The Capital Taxes Group of The Institute for Fiscal Studies (Institute for Fiscal Studies (IFS), 1994)
The taxation of savings in the UK is in a mess and the IFS Capital Taxes Group, set up in 1987 and chaired by Malcolm Gammie of Linklaters & Paines, makes proposals which would considerably simplify the system. Its two principal proposals, which are outlined in this report, are for an extension of the current PEP and TESSA regimes to all personal savings and the introduction of an allowance for the cost of equity finance.
Keywords: 330